Ansiedade e depressão entre estudantes da Universidade Federal do Espírito Santo após o retorno ao ensino presencial durante a pandemia por COVID-19 - Silva, Bruna Martins (2023)
Introduction. The pandemic of the disease caused by the new coronavirus (COVID-19) has led to changes in the behavior and routine of university students, which has had an impact on the development of a series of common mental disorders, such as anxiety and depression. Despite the impact of these disorders on academic performance, to date, there are no studies investigating this issue among Brazilian university students after returning to face-to-face teaching. Goal. Understanding aspects related to anxiety and depression symptoms in university students after returning to face-to-face teaching during the COVID-19 pandemic. Method. This is a cross-sectional, quantitative study, carried out between July 2022 and August 2022. University students, over 18 years old, linked to the Federal University of Espírito Santo (UFES) were included in the research. Sampling was carried out for convenience and data collection was performed through a questionnaire, implemented on the SurveyMonkey online platform. Sociodemographic data and data related to the use of pharmacological and non-pharmacological measures used to treat anxiety and depression symptoms in university students were collected. In addition, students answered the screening and severity measurement questionnaires for symptoms of anxiety and depression: General Anxiety Disorder (GAD-7) and Patient Health Questionnaire-9 (PHQ-9), respectively. Data were analyzed using descriptive and inferential statistics. This work was approved by the Ethics Committee for Research with Human Beings and all participants signed the Free and Informed Consent Term (TCLE). Results. 1103 students participated in the study. Based on the results of the GAD-7 and PHQ-9 scales, it was observed that 8.3% (n=92) of the students had scores compatible with anxiety, 14.7% (n=162) with scores compatible with depression, and 56 .7% (n= 625) scores compatible with anxiety and depression simultaneously. 1103 students participated in the study. Based on the results of the GAD-7 and PHQ-9 scales, it was observed that 8.3% (n=92) of the students had scores compatible with anxiety, 14.7% (n=162) with scores compatible with depression, and 56 .7% (n= 625) scores compatible with anxiety and depression simultaneously. In addition, 422 (38.3%) of the students had thoughts related to self-harm or suicide in the last fifteen days. It was observed that 37% (n=409) of the participants reported having a previous diagnosis of anxiety and/or depression. Regarding the treatment of anxiety and depression, 62.3% (n=255) of the students reported using pharmacological measures, such as selective serotonin reuptake inhibitors (64.2%; n=164), benzodiazepines (45, 1%; n=115) and serotonin and noradrenaline reuptake inhibitors (23.5%; n=60) were the most mentioned, while 36.7% (n=150) use psychotherapy, 14.9% (n=61) meditation and 6.4% (n=26) yoga. Conclusion. Through the data found, it can be concluded that the COVID-19 pandemic had an impact on the mental health of university students, providing a high frequency of scores compatible with anxiety and/or depression and increasing the search for pharmacological management to relieve the symptoms of these disorders, which is why it is essential for the university to engage in guaranteeing the protection, promotion and recovery of students' mental health during and after the COVID-19 pandemic.